Identification and Characterization of Circular RNA as a Novel Regulator and Biomarker in Preterm Birth - Ran, Yuxin; Yin, Nanlin; Huang, Dongni; Zhao, Yangyu; Yang, Jing; Zhang, Hanwen; Qi, Hongbo (Frontiers in Bioengineering and Biotechnology, 2020)
Premature birth (PTB), as the leading cause of neonatal death, is a severe threat to maternal-fetal health. The diagnosis and treatment of PTB are difficult as its underlying mechanism still unknown. Circular RNA (circRNA) is an emerging molecule that plays an essential role in the pathological processes of various diseases. However, it is still unclear whether circRNAs are abnormal or involves in the PTB pathology. In this study, we analyzed RNA-seq data of peripheral blood from preterm and term pregnant women and verified with microarray data. There were 211 circRNA expression disorders in PTB, of which 68 increased and 143 decreased. Bioinformatics analysis revealed that the top 20 circRNAs competitively bind 68 miRNAs, thereby regulating 622 mRNAs mainly related to immunity, inflammation, and nerve activity, which may ultimately contribute to the occurrence of PTB. Moreover, 6 regulatory pairs, including hsa-MORC3_0001--hsa-miR-1248--CHRM2 were the core parts of this mechanism network, which might be therapeutic targets for PTB. Besides, ROC analysis indicated that hsa-ANKFY1_0025, hsa-FAM13B_0019, and hsa-NUSAP1_0010 (AUC=0.7138, 0.9589, 1.000) have an excellent discrimination ability for PTB. Taken together, we explored for the first time the circRNA expression profile of PTB, and analyze its regulatory mechanism and predictive value for PTB, thus bringing new light to the diagnosis and treatment of PTB.